The newmedical treatment procedure of the German Statutory Accident Insurance: From the perspective of BG hospitals - Buehren, V.; Perl, Mario (Unfallchirurg, 2016)
The Hospital Group of the Statutory Accident Insurance (BG hospitals) was affected by the new requirements for severe injury procedures (SAV) in the same manner as all other maximum care hospitals. Simultaneously, the BG clinics were merged to form a centrally organized hospital group. A substantial need for adjustment existed for specialties, such as neurosurgery and visceral surgery at some sites. Needless to say, all trauma victims benefit from the high standards required by the Statutory Accident Insurance regardless of their insurance status. The provision of medical treatment with respect to its implementation into routine practice must be further optimized and additions, e.g. for the occurrence of complications are necessary.
Keywords: Concentration process; Centralization; German Statutory Accident Insurance; Severe injury procedures (SAV); Injury procedures (VAV)